Nietzsche e o eruditismo: introdução a uma nova concepção de formação - Figueira, Felipe Luiz Gomes [UNESP] (2015)
This thesis' objective is to investigate Nietzsche's criticism on eruditism in his later years' writings, and our hypothesis is that eruditism interditates/minimizes a singularized formation in relation to the herd. Eruditism will be identified as the incarnation of the moralizing conception of formation, that can be synthesized thru the formula presented in Beyond good and evil: knowledge by knowledge - here is the last trap set by moral. Under this perspective it will be possible to understand the way the German philosopher will try to build a new concept of formation, that we will call transvalued formation. The moralizing formation, that tries to subjugate the individual under extreme parameters, marginalize and suffocate life experiences. Nietzsche proposes and worries with the formation of a single individual, as he says in Aurora. And for this single individual it is necessary that the formation don't be presumed even remotely what it is, that is, that the formation doesn't close in itself, but that it keeps itself permanently open, free.